STRETCHING EXERCISE UNTUK MENGATASI DISMINORHOE PRIMER - Hamimatus Zainiyah; Alis Nurdiana (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2019)
Primary dysmenorrhea is a feeling of pain in the lower abdomen that occurs due to hormonal imbalance, without any abnormalities in the pelvic organs. Primary dysmenorrheam will affect 60–75% of young women. In Indonesia, the incidence of dysmenorrhea reaches 64.25%, 54.89% experiences primary dysmenorrhea, and the remaining 9.36% experiences secondary dysmenorrhea (Santoso, 2008). Based on a preliminary study conducted on grade VII students of SMPN 5 Bangkalan, it was found that 87% of students had mild dysmenorrhea, 9% of students had moderate dysmenorrhea, 4% had severe dysmenorrhea. The method used to carry out community service is by collecting data on the number of grade VII students at SMPN 5 Bangkalan, then conducting interviews with students about understanding primary dysmenorrhea and how to overcome it. The activity was continued with abdominal stretching exercise which was held at SMPN 5 Bangkalan. The participants of the activity were 80 students of SMPN 5 Bangkalan who participated in the training activities. While participating in the activities, students were very enthusiastic about the material presented. The students were also able to do abdominal stretching exercises to treat primary dysmenorrhea. The results of the pain scale of 80 respondents found that 20 experienced primary dysmenorrhea with mild pain, mostly 10 students (50%) before training. Meanwhile, after the training, all 20 students were painless (100%).